Evaluasi Program Praktik Pengalaman Lapangan (PPL) STAB Maha Prajna Tahun 2024 Dengan Model CIPP - Nyaman (Sekolah Tinggi Agama Buddha Maha Prajna Jakarta, 2025)
Abstract This study aims to comprehensively evaluate the implementation of the Field Experience Program (PPL) for students of the Buddhist Religious Education Study Program at STAB Maha Prajna in 2024. Using the CIPP (Context, Input, Process, Product) evaluation model with a qualitative descriptive approach, this research examines all stages of the program through observation, interviews, and documentation study. The evaluation results identified several areas for optimization. In the context dimension, the alignment of the program's objectives with the institution's vision is excellent, but potential for refinement in the committee structure was found to enhance the effectiveness of the mentoring process. From the input aspect, student qualifications met the requirements, while coordination with partner schools showed room for improvement, particularly regarding schedule synchronization. Furthermore, in the process stage, the program's execution highlighted the importance of strengthening communication regarding student roles and increasing the intensity of supervision. From the product side, a disparity was noted between the highly satisfactory quantitative results and the qualitative findings in the field, indicating an opportunity to enrich the variety of teaching methods and improve consistency in the mentoring process. This study recommends improvements in management, reinforcement of external coordination, and optimization of supervision quality to align the program's ideal objectives with its on-the-ground implementation. Keywords: Program Evaluation, Field Experience Program, CIPP Model.